'Let's talk more about this': An analysis of how experts engage novice physicians in pedagogical dialogue. (30th December 2016) - Awad Scrocco, Diana
Abstract : This exploratory study examines conversations between faculty physician preceptors and resident physicians to identify communicative actions that encourage pedagogical dialogue. Using a modified grounded theory approach, this study considers resident-preceptor conversations at the levels of the conversational exchange and the clause. Four categories of exchanges emerged from the analysis: presenting the case, teaching clinical concepts, initiating clinical discussion, and offering/requesting direct instruction. Focusing on the latter two categories, this study identifies common communicative actions in the clauses of speakers' conversational turns. I contend that clinical-discussion exchanges best support the academic goal of these conversations by engaging novices with open-ended, interpretation-focused questions, proposals, and assessments; in contrast, direct-instruction exchanges support the workplace objective of treating patients through imperative proposals and procedure-focused questions and assessments. This analysis offers communication scholars insight into how expert-novice conversations support professionalization and provides preceptors with an understanding of communicative actions that may facilitate pedagogical dialogue.